Potential Effects of Bigheaded Carps on Four Laurentian Great Lakes Food Webs. (9th March 2021) - Rutherford, Edward S.; Zhang, Hongyan; Kao, Yu‐Chun; Mason, Doran M.; Shakoor, Ali; Bouma‐Gregson, Keith; Breck, Jason T.; Lodge, David M.; Chadderton, W. Lindsay
Abstract: Bigheaded carps (BHCs; Silver Carp Hypophthalmichthys molitrix and Bighead Carp H. nobilis ) are economically and culturally important in Asia and Europe but are considered highly invasive throughout the Mississippi River watershed and pose a threat to the food web and fisheries of the Laurentian Great Lakes. We used the Ecopath with Ecosim model framework to evaluate potential risk of BHC population growth and food web effects in four Great Lakes habitats, including mesotrophic waters of Saginaw Bay (Lake Huron) and Lake Erie and the oligotrophic main basins of Lakes Michigan and Huron. We simulated BHC population growth and food web effects under different scenarios of BHC production rates, prey vulnerability to BHCs, and availability of age‐0 BHCs to predation by salmonines. In the main basins of Lakes Michigan and Huron, the projected BHC population growth was low or negative, with a projected final BHC biomass of 0.5–1.1 times the initial introductory biomass (2% of total fish biomass for each BHC species), and BHCs had negligible effects on most food web groups across all scenarios. In contrast, in Saginaw Bay and Lake Erie, the projected BHC biomass was 2.5–12.5 times higher than the initial biomass across all scenarios, and the largest increases occurred under scenarios of high prey vulnerability to BHCs and high BHC production rates. High projected BHC biomass in Saginaw Bay and Lake Erie had negative effects on zooplankton and planktivorous fish groups and mixed effects on piscivores but had relatively negligible effects on most other food web groups across all scenarios. Our results are consistent with reported BHC effects on food webs in the Mississippi River and its tributaries and inform efforts to prevent BHC invasion of the Great Lakes.